Limits of Conditionality in Poverty Reduction Programs - Dell'Ariccia, Giovanni; Cordella, Tito. (Washington, D.C. : International Monetary Fund, 2002)
When donors and recipients have different preferences over budgetary allocations, conditionality helps the implementation of donor-financed poverty reduction programs. However, if donors cannot perfectly monitor all recipients' actions, conditionality entails an inefficient allocation of resources. Under such conditions, the optimal amount of conditionality varies (often not monotonically) with the recipients' degree of social commitment. Finally, if recipients' preferences are not observable, conditionality can be used to prevent recipients with a weak commitment to poverty reduction from obtaining aid funds. This may however lead to further distortions in terms of resource allocation and to phenomena of "aid rationing.".
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Government Policy; Provision and Effects Of Welfare Program; WP